Biofilm-associated transformation of polylactic acid (PLA) microbeads by single- and dual-species bacterial communities - Xinting Hu; Stephan Heeb; Honglei Zhang; Enrico Marsili (Journal of Hazardous Materials, 2026)

Mushroom‐shaped structures formed in Acinetobacter baumannii biofilms grown in a roller bioreactor are associated with quorum sensing–dependent Csu‐pilus assembly - Manuel Romero; Celia Mayer; Stephan Heeb; Krittanont Wattanavaekin; Miguel Cámara; Ana Otero; Paul Williams (Environmental Microbiology, 2022)
Summary There is currently a need to develop simple biofilm models that facilitate investigation of the architecture/biology of mature bacterial biofilms in a consistent/standardized manner given their environmental and clinical importance and the need for new anti‐biofilm interventions. This study introduces a novel biofilm culture system termed the rolling biofilm bioreactor (RBB). This easily operated system allows adherent microbial cells to be repeatedly exposed to air/solid/liquid interfaces optimizing biofilm growth. The RBB was exploited to investigate biofilm formation in Acinetobacter baumannii . High levels of A . baumannii biofilm biomass reproducibly accumulate in the RBB and, importantly, undergo a maturation step to form large mushroom‐shaped structures that had not been observed in other models. Based on image analysis of biofilm development and genetic manipulation, we show how N ‐acylhomoserine lactone‐dependent quorum sensing (QS) impacts on biofilm differentiation, composition and antibiotic tolerance. Our results indicate that extracellular DNA (eDNA) is a key matrix component in mature Acinetobacter biofilms as the mushroom‐like structures consist of dense cellular masses encased in an eDNA mesh. Moreover, this study reveals the contribution of QS to A . baumannii biofilm differentiation through Csu pilus assembly regulation. Understanding the mechanisms of structural development of mature biofilms helps to identify new biofilm eradication and removal strategies.

2‐Tridecanone impacts surface‐associated bacterial behaviours and hinders plant–bacteria interactions - Isabel M. López‐Lara; Joaquina Nogales; Ángel Pech‐Canul; Nieves Calatrava‐Morales; Lydia M. Bernabéu‐Roda; Paloma Durán; Virginia Cuéllar; José Olivares; Laura Alvarez; Diana Palenzuela‐Bretones; Manuel Romero; Stephan Heeb; et al. (Environmental Microbiology, 2018)
Summary Surface motility and biofilm formation are behaviours which enable bacteria to infect their hosts and are controlled by different chemical signals. In the plant symbiotic alpha‐proteobacterium Sinorhizobium meliloti , the lack of long‐chain fatty acyl‐coenzyme A synthetase activity (FadD) leads to increased surface motility, defects in biofilm development and impaired root colonization. In this study, analyses of lipid extracts and volatiles revealed that a fadD mutant accumulates 2‐tridecanone (2‐TDC), a methylketone (MK) known as a natural insecticide. Application of pure 2‐TDC to the wild‐type strain phenocopies the free‐living and symbiotic behaviours of the fadD mutant. Structural features of the MK determine its ability to promote S. meliloti surface translocation, which is mainly mediated by a flagella‐independent motility. Transcriptomic analyses showed that 2‐TDC induces differential expression of iron uptake, redox and stress‐related genes. Interestingly, this MK also influences surface motility and impairs biofilm formation in plant and animal pathogenic bacteria. Moreover, 2‐TDC not only hampers alfalfa nodulation but also the development of tomato bacterial speck disease. This work assigns a new role to 2‐TDC as an infochemical that affects important bacterial traits and hampers plant–bacteria interactions by interfering with microbial colonization of plant tissues.

The Pseudomonas putida CsrA/RsmA homologues negatively affect c‐di‐GMP pools and biofilm formation through the GGDEF/EAL response regulator CfcR - Óscar Huertas‐Rosales; Manuel Romero; Stephan Heeb; Manuel Espinosa‐Urgel; Miguel Cámara; María Isabel Ramos‐González (Environmental Microbiology, 2017)
Summary Expression of cfcR , encoding the only GGDEF/EAL response regulator in Pseudomonas putida , is transcriptionally regulated by RpoS, ANR and FleQ, and the functionality of CfcR as a diguanylate cyclase requires the multisensor CHASE3/GAF hybrid histidine kinase named CfcA. Here an additional level of cfcR control, operating post‐transcriptionally via the RNA‐binding proteins RsmA, RsmE and RsmI, is unraveled. Specific binding of the three proteins to an Rsm‐binding motif (5′CANGGANG3′) encompassing the translational start codon of cfcR was confirmed. Although RsmA exhibited the highest binding affinity to the cfcR transcript, single deletions of rsmA , rsmE or rsmI caused minor derepression in CfcR translation compared to a ΔrsmIEA triple mutant. RsmA also showed a negative impact on c‐di‐GMP levels in a double mutant ΔrsmIE through the control of cfcR , which is responsible for most of the free c‐di‐GMP during stationary phase in static conditions. In addition, a CfcR‐dependent c‐di‐GMP boost was observed during this stage in ΔrsmIEA confirming the negative effect of Rsm proteins on CfcR translation and explaining the increased biofilm formation in this mutant compared to the wild type. Overall, these results suggest that CfcR is a key player in biofilm formation regulation by the Rsm proteins in P. putida .

Biotic inactivation of the P seudomonas aeruginosa quinolone signal molecule - Eliza Ye‐Chen Soh; Siri R. Chhabra; Nigel Halliday; Stephan Heeb; Christine Müller; Franziska S. Birmes; Susanne Fetzner; Miguel Cámara; Kok‐Gan Chan; Paul Williams (Environmental Microbiology, 2015)
Summary In P seudomonas aeruginosa , quorum sensing ( QS ) regulates the production of secondary metabolites, many of which are antimicrobials that impact on polymicrobial community composition. Consequently, quenching QS modulates the environmental impact of P . aeruginosa . To identify bacteria capable of inactivating the QS signal molecule 2‐heptyl‐3‐hydroxy‐4(1 H )‐quinolone ( PQS ), a minimal medium containing PQS as the sole carbon source was used to enrich a M alaysian rainforest soil sample. This yielded an A chromobacter xylosoxidans strain ( Q 19) that inactivated PQS , yielding a new fluorescent compound ( I ‐ PQS ) confirmed as PQS ‐derived using deuterated PQS . The I ‐ PQS structure was elucidated using mass spectrometry and nuclear magnetic resonance spectroscopy as 2‐heptyl‐2‐hydroxy‐1,2‐dihydroquinoline‐3,4‐dione ( HHQD ). A chromobacter xylosoxidans Q 19 oxidized PQS congeners with alkyl chains ranging from C 1 to C 5 and also N ‐methyl PQS , yielding the corresponding 2‐hydroxy‐1,2‐dihydroquinoline‐3,4‐diones, but was unable to inactivate the PQS precursor HHQ . This indicates that the hydroxyl group at position 3 in PQS is essential and that A . xylosoxidans inactivates PQS via a pathway involving the incorporation of oxygen at C 2 of the heterocyclic ring. The conversion of PQS to HHQD also occurred on incubation with 12/17 A . xylosoxidans strains recovered from cystic fibrosis patients, with P . aeruginosa and with A rthrobacter , suggesting that formation of hydroxylated PQS may be a common mechanism of inactivation.

The G ac/ R sm and cyclic‐di‐ GMP signalling networks coordinately regulate iron uptake in P seudomonas aeruginosa - Emanuela Frangipani; Daniela Visaggio; Stephan Heeb; Volkhard Kaever; Miguel Cámara; Paolo Visca; Francesco Imperi (Environmental Microbiology, 2014)
Summary P seudomonas aeruginosa is a versatile bacterial pathogen capable of occupying diverse ecological niches. To cope with iron limitation, P . aeruginosa secretes two siderophores, pyoverdine and pyochelin, whose ability to deliver iron to the cell is crucial for biofilm formation and pathogenicity. In this study, we describe a link between iron uptake and the G ac/ R sm system, a conserved signal transducing pathway of P . aeruginosa that controls the production of extracellular products and virulence factors, as well as the switch from planktonic to biofilm lifestyle. We have observed that pyoverdine and pyochelin production in P . aeruginosa is strongly dependent on the activation state of the G ac/ R sm pathway, which controls siderophore regulatory and biosynthetic genes at the transcriptional level, in a manner that does not involve regulation of ferric uptake regulator ( F ur) expression. G ac/ R sm‐mediated regulation of iron uptake genes appears to be conserved in different P . aeruginosa strains. Further experiments led to propose that the G ac/ R sm system regulates siderophore production through modulation of the intracellular levels of the second messenger c‐di‐ GMP , indicating that the c‐di‐ GMP and the G ac/ R sm regulatory networks essential for biofilm formation can also coordinately control iron uptake in P . aeruginosa .

The Pseudomonas aeruginosa sensor RetS switches Type III and Type VI secretion via c‐di‐GMP signalling - Joana A. Moscoso; Helga Mikkelsen; Stephan Heeb; Paul Williams; Alain Filloux (Environmental Microbiology, 2012)

The Pseudomonas aeruginosa sensor RetS switches Type III and Type VI secretion via c‐di‐GMP signalling - Joana A. Moscoso; Helga Mikkelsen; Stephan Heeb; Paul Williams; Alain Filloux (Environmental Microbiology, 2011)
Summary Acute bacterial infections are associated with motility and cytotoxicity via the type III secretion system (T3SS), while chronic infections are linked to biofilm formation and reduced virulence. In Pseudomonas aeruginosa , the transition between motility and sessility involves regulatory networks including the RetS/GacS sensors, as well as the second messenger c‐di‐GMP. The RetS/GacS signalling cascade converges on small RNAs, RsmY and RsmZ, which control a range of functions via RsmA. A retS mutation induces biofilm formation, and high levels of c‐di‐GMP produce a similar response. In this study, we connect RetS and c‐di‐GMP pathways by showing that the retS mutant displays high levels of c‐di‐GMP. Furthermore, a retS mutation leads to repression of the T3SS, but also upregulates the type VI secretion system (T6SS), which is associated with chronic infections. Strikingly, production of the T3SS and T6SS can be switched by artificially modulating c‐di‐GMP levels. We show that the diguanylate cyclase WspR is specifically involved in the T3SS/T6SS switch and that RsmY and RsmZ are required for the c‐di‐GMP‐dependent response. These results provide a firm link between the RetS/GacS and the c‐di‐GMP pathways, which coordinate bacterial lifestyles, as well as secretion systems that determine the infection strategy of P. aeruginosa .

Transcriptomic analysis reveals a global alkyl‐quinolone‐independent regulatory role for PqsE in facilitating the environmental adaptation of Pseudomonas aeruginosa to plant and animal hosts - Giordano Rampioni; Christian Pustelny; Matthew P. Fletcher; Victoria J. Wright; Mary Bruce; Kendra P. Rumbaugh; Stephan Heeb; Miguel Cámara; Paul Williams (Environmental Microbiology, 2010)
Summary The quorum sensing (QS) system of Pseudomonas aeruginosa constitutes a sophisticated genome‐wide gene regulatory network employing both N ‐acylhomoserine lactone and 2‐alkyl‐4‐quinolone (AQ) signal molecules. AQ signalling utilizes 2‐heptyl‐3‐hydroxy‐4‐quinolone (PQS) and its immediate precursor, 2‐heptyl‐4‐quinolone (HHQ). AQ biosynthesis requires the first four genes of the pqsABCDE operon and while the biochemical function of pqsE is not known, it is required for the production of secondary metabolites such as pyocyanin. To gain insights into the relationship between the AQ stimulon, the PqsE stimulon and the regulatory function of PqsE, we constructed a pqsE inducible mutant ( pqsE ind) and compared the transcriptomes of the induced and uninduced states with a pqsA mutant. Of 158 genes exhibiting altered expression in the pqsA mutant, 51% were also affected in the pqsE mutant. Following induction of pqsE , 237 genes were differentially expressed compared with the wild‐type strain. In the pqsE ind strain, pqsA was highly expressed but following induction both pqsA expression and AQ biosynthesis were repressed, revealing a negative autoregulatory role for PqsE. Furthermore, pqsE was required for swarming motility and virulence in plant and animal infection models in the absence of AQs, while mature biofilm development required both pqsA and pqsE . Taken together these data reveal that PqsE is a key regulator within the QS circuitry facilitating the environmental adaptation of P. aeruginosa .